2022
DOI: 10.47115/jshs.1165792
|View full text |Cite
|
Sign up to set email alerts
|

Hemodiyaliz Hastalarının Manevi Durumlarının Umutsuzluk Düzeylerine Etkisi

Abstract: Aim: This study was conducted descriptively to determine the effects of the spiritual orientation of hemodialysis patients on their levels of hopelessness. Method: The study sample consisted of 100 hemodialysis patients treated at Ondokuz Mayıs University Health Application and Research Center (OMUHARC) hemodialysis unit, nephrology service and City Health Center affiliated to OMUHARC between July 2017 and May 2018. The data were collected using patient introductory information forms, Spiritual Orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…The results of the research study by Atan et al (2020) were in a similar vein to the findings of the current research and indicated that having an additional chronic disease increased hopelessness. In other research studies in the relevant literature, having a secondary disease besides the pre-existing one led to an increase in the patient's hopelessness level (Günaydın & Özdelikara, 2022). The finding of this current study is similar to the results in the relevant literature.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the research study by Atan et al (2020) were in a similar vein to the findings of the current research and indicated that having an additional chronic disease increased hopelessness. In other research studies in the relevant literature, having a secondary disease besides the pre-existing one led to an increase in the patient's hopelessness level (Günaydın & Özdelikara, 2022). The finding of this current study is similar to the results in the relevant literature.…”
Section: Discussionsupporting
confidence: 90%
“…Başaran et al (2016) found that the mean hopelessness score of the patients undergoing hemodialysis therapy was 12.76 ± 3.04 points.and this mean of scores is similar to the one obtained in this current study. Günaydın and Özdelikara (2022) found that the mean hopelessness score of the patients undergoing hemodialysis therapy was 5.68±4.43 points.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation